“Nobody Seemed to Notice My Work”: The Lived Experiences of Home Care Workers Assisting People With Chronic Diseases: A Phenomenological Study - Valentina Cacciapuoti; Silvio Simeone; Michele Virgolesi; Medeline R. Sterling; Elisa Dallago; Ercole Vellone; Rosaria Alvaro; Gianluca Pucciarelli (Journal of Primary Care & Community Health)
Introduction: Home care workers (HCWs) are paid caregivers who provide support to patients with chronic conditions and functional limitations. Additionally, they provide emotional support to patients and familial support. Although several qualitative studies have been conducted on HCWs, they focused more on studying prevalently the lived experiences about the workplace violence, the end of life, stressor and resilience, during the COVID-19 pandemic or focused more in dementia and heart failure, but not on feelings and working conditions. Methods: The study was carried out using Cohen’s phenomenological methodology. The subjects were enrolled in several cities of Central Italy and interviewed with open questions to allow them full freedom of expression and asked to describe their lived experience of HCWs who helped people with chronic diseases. Each interview was recorded audio and lasted between 20 and 60 min. Researchers involved in the analysis were independently immersed in the data by reading and rereading the transcripts to gain a sense of the entire data set. The extrapolation of the themes followed. The individual researchers compared the various extrapolated themes. Results: Seventeen HCWs, all women, with a mean age of 54 years were enrolled in this study. All had more than a year (from 4 to 26 years) of experience in Italy, and almost the whole sample lived with the person they were assisting. Three themes were identified in the interviews: (1) feeling inadequate as a nurse, (2) feeling valued in this role, and (3) uncertain future. Feeling inadequate due to lack of training, difficulties related to the Italian language, or uncertainty about their future were topics identified by the HCWs. Conclusions: Since HCWs represent an important resource which, if properly trained, could positively influence the quality of life of the elderly population and a valid support for their families, understanding the lived experience can suggest interventions that could be implemented by a health care professional and provide evidence to inform political decision makers to increase the support for HCWs.